1966
DOI: 10.1128/jb.92.1.63-71.1966
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Metabolism of Marine Bacteria XV. Relation of Na + -Activated Transport to the Na + Requirement of a Marine Pseudomonad for Growth

Abstract: MATULA, AND ROBERT A. MAcLEOD. Nutrition and metabolism of marine bacteria. XV. Relation of Na+-activated transport to the Na+ requirement of a marine pseudomonad for growth. J. Bacteriol. 92:63-71. 1966.-A marine pseudomonad was found to require 50 to 100 mm Na+ for maximal rate of oxidation of D-galactose and for the transport of D-fucose-H3 into the cells. The same organism required 150 to 200 mm Na+ for the oxidation of L-alanine and for the transport of 4-aminoisobutyric acid-C'4 (AIB-C14) into the cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 16 publications
3
33
0
Order By: Relevance
“…Paper chromatography of extracts of cells nearly saturated with labeled AIB showed a single peak of radioactivity corresponding to unlabeled AIB. This is in agreement with observations in bacteria (6,23,30), as well as eukaryotic systems including Crithidiafasciculata ( 1 9) and mammalian cells (2,29,31). AIB is nonmetabolizable due to the absence of an a-hydrogen that normally allows tautomeric changes of pyridoxal derivatives necessary for degradation (5).…”
Section: Discussionsupporting
confidence: 91%
“…Paper chromatography of extracts of cells nearly saturated with labeled AIB showed a single peak of radioactivity corresponding to unlabeled AIB. This is in agreement with observations in bacteria (6,23,30), as well as eukaryotic systems including Crithidiafasciculata ( 1 9) and mammalian cells (2,29,31). AIB is nonmetabolizable due to the absence of an a-hydrogen that normally allows tautomeric changes of pyridoxal derivatives necessary for degradation (5).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies with whole cells of this organism have been interpreted as indicating that Na+ has two functions in these cells. One function, which is highly specific for Na+, is involved in the uptake of 14C-AIB (14,37), and the other, which can be carried out at least partially by Li+, prevents the release of the accumulated compound by the cells (37). Since protoplasts and whole cells had the same quantitative requirements for Na+ for uptake of 54C-AIB and since Li+ exerted the same degree of sparing action on the Na+ requirement, it can be concluded that both functions of Na+ are carried out at the level of the cytoplasmic membrane.…”
Section: Resultsmentioning
confidence: 99%
“…This requirement is specific and is independent of an osmotic function since growth does not occur in a medium in which sodium is replaced by equimolar amounts of other monovalent cations (33,34). In the case of two species of marine bacteria, it has been shown that their permease systems require sodium for the uptake of exogenous substrates (17). The sodium ion requirement of many or all bacteria of marine origin has led to the suggestion that this property may serve to distinguish marine bacteria from soil and fresh water strains (33,34).…”
mentioning
confidence: 99%